Hericium erinaceus and Coriolus versicolor Modulate Molecular and Biochemical Changes after Traumatic Brain Injury - Ramona D'Amico; Angela Trovato Salinaro; Roberta Fusco; Marika Cordaro; Daniela Impellizzeri; Maria Scuto; Maria Laura Ontario; Gianluigi Lo Dico; Salvatore Cuzzocrea; Rosanna Di Paola; Rosalba Siracusa; Vittorio Calabrese (MDPI AG, 2021)
Traumatic brain injury (TBI) is a major health and socioeconomic problem affecting the world. This condition results from the application of external physical force to the brain which leads to transient or permanent structural and functional impairments. TBI has been shown to be a risk factor for neurodegeneration which can lead to Parkinson's disease (PD) for example. In this study, we wanted to explore the development of PD-related pathology in the context of an experimental model of TBI and the potential ability of Coriolus versicolor and Hericium erinaceus to prevent neurodegenerative processes. Traumatic brain injury was induced in mice by controlled cortical impact. Behavioral tests were performed at various times: the animals were sacrificed 30 days after the impact and the brain was processed for Western blot and immunohistochemical analyzes. After the head injury, a significant decrease in the expression of tyrosine hydroxylase and the dopamine transporter in the substantia nigra was observed, as well as significant behavioral alterations that were instead restored following daily oral treatment with Hericium erinaceus and Coriolus versicolor. Furthermore, a strong increase in neuroinflammation and oxidative stress emerged in the vehicle groups. Treatment with Hericium erinaceus and Coriolus versicolor was able to prevent both the neuroinflammatory and oxidative processes typical of PD. This study suggests that PD-related molecular events may be triggered on TBI and that nutritional fungi such as Hericium erinaceus and Coriolus versicolor may be important in redox stress response mechanisms and neuroprotection, preventing the progression of neurodegenerative diseases such as PD.